Natural Compounds of the Birch Polypore Piptoporus betulinus (Bull.) P. Karst: an Overview of Biological Activities - Tiupova, Tetiana; Tkachenko, Halina; Kurhaluk, Natalia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2025)
Piptoporus betulinus (Bull.) P. Karst, commonly known as the birch polypore, is a medicinal fungus traditionally used in Europe and Asia for the treatment of various ailments, including infections, inflammations, and gastrointestinal disorders. Recent scientific interest has highlighted the rich phytochemical composition and pharmacological potential of this polypore. The mushroom contains a wide range of bioactive compounds such as polysaccharides, triterpenoids, phenolics, and lectins, which contribute to its anti-inflammatory, antioxidant, antimicrobial, and anticancer activities. These effects are mediated by diverse mechanisms, including immunomodulation, suppression of inflammatory signalling, inhibition of microbial proliferation, and induction of apoptosis in tumour cells. This review synthesises current knowledge on the biological properties of P. betulinus, drawing on both ethnopharmacological data and modern biomedical research. Preliminary results from investigations into the antioxidant properties of the fungus are also presented. The therapeutic versatility of P. betulinus suggests its potential role in the prevention and treatment of chronic and degenerative diseases, especially those related to oxidative stress and inflammation. Furthermore, the integration of P. betulinus-derived natural products into functional foods, dietary supplements or topical formulations may offer novel approaches to support health and well-being. With the growing interest in evidence-based natural remedies, this species is a promising candidate for the development of alternative or complementary therapies. However, well-designed in vivo studies and clinical trials remain essential to establish standardised use, safety parameters, and bioavailability of their active compounds.